THE OVERVIEW OF INDONESIAN MINISTRY OF TRANSPORTATION’S MOBILE GEOGRAPHIC INFORMATION SYSTEM APLICATION - Istiyanto, Bambang; Rizal, Yan El; Rizka, Mouli De; Brilianti, Dani F. (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Traffic information is an important necessity for humans. Advances in technology make various facilities. The use of smart phone is already very common thing. The use of smart phones, especially development based on open source license is very favorable. Any individual or organization can create applications that can be accessed by many people. There are various applications on smart phone device that is associated with the map -based transportation. Staring from the application issued by government agencies to the application made by the individual. One of the legal application based map application issued by the agency is MoT GIS or known as "GIS KEMENHUB". This application issued by the Ministry of Transportation. Problem for user is the limitations of information that can be obtained from the features.  Applications are found to be the maximum that is less attractive to users. The purpose of this study was to determine how the advantages and disadvantages of the user application. Advantages and disadvantages which were known from the user side could be input for the development of better applications. This study contained the discussion of the current state of the application. Object current application was the basis for the development of applications, input from external users who were not part of the developer to add a new angle in the subsequent development. The use of applications generated by government agencies were legally expected to reduce mistrust users to use the data including map data. Legal institutions were expected to generate data in accordance with clear standards. This application is not directly related to the system or management of transportation, however the use of application based on the appropriate map can asses the transportation easily.